EVALUASI KAPASITAS PRODUKSI BAN MENGGUNAKAN METODE RCCP DENGAN PENDEKATAN BOLA - Tigar Putri Adhiana; Indro Prakoso; Nidya Pangestika (Universitas Putera Batam, 2020)
Capacity planning in a company's production process needs to be considered so that the products produced meet consumer demand. PT X, is a manufacturing company that focuses on tire production. One type of large-sized tire product that has the highest demand is the ABC type with a sTabel production amount per month and demand that goes up every year. In terms of fulfilling customer demand, especially requests for large tires with type ABC, PT X often has difficulty in meeting consumer demand, this happens because the capacity of the machine is not available. Therefore, the existing production capacity must be evaluated to find out whether the available capacity is sufficient with the required capacity. To analyze this problem, the Rough Cut Capacity Planning (RCCP) method, this method is to analyze and test the determination of capacity in the master production schedule. Calculation of available capacity and capacity required in a year is carried out for the process carried out, namely: Building, Spreading and venting, curing, and Trimming. For the building and trimming process, it is found that the decision of the acupacity is fulfilled, while the Spreading and venting process is required to add 1 machine, and the curing process is required to add the machine according to the number of requests per month. From these results it can be given a proposal that needs to be considered in meeting the capacity to meet consumer needs while still paying attention to production costs.